2017
DOI: 10.3906/zoo-1510-4
|View full text |Cite
|
Sign up to set email alerts
|

First record of water bears (Tardigrada) from sponges (Porifera)

Abstract: Aquatic species of Tardigrada usually inhabit submerged plants or sediment but they are also known as associated with other animals, like barnacles (Crustacea: Cirripedia) or sea cucumbers (Echinodermata: Holothuroidea). In sponges collected from Lake Ohrid (Macedonia) we found individuals of two tardigrade taxa: Isohypsibius sp. and Dactylobiotus sp. This paper provides the first record of Tardigrada from Macedonia (Lake Ohrid) and is the first report of these animals on sponges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In addition, there may be animal and debris vectors attached to seaweed (Steiner 1926), drift wood (Miller, Clark, and Miller 2012), or a barnacle on a crab or turtle could facilitate movement. Aquatic tardigrades have been reported on the algae and biofilm found on freshwater sponges in Turkey (Talandai and Zawierucha 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there may be animal and debris vectors attached to seaweed (Steiner 1926), drift wood (Miller, Clark, and Miller 2012), or a barnacle on a crab or turtle could facilitate movement. Aquatic tardigrades have been reported on the algae and biofilm found on freshwater sponges in Turkey (Talandai and Zawierucha 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect evidence of non-wind dispersal has been found in the discovery in North America of Central and South American species which do not have a logical wind pathway. A Costa Rican species (Spears et al 2013) has also been found in Kansas, a southern hemisphere genus has been found in Alaska (Calloway et al 2011), and a species recently described from Argentina was discovered in the canopy of Kansas trees (Tibbs, Emanuels, and Miller 2016).…”
Section: Introductionmentioning
confidence: 99%